PERBANDINGAN JENIS KONSUMSI AIR MINUM DENGAN KRISTALURIA PADA ANAK - Umboh, Adrian; Umboh, Valentine (JKK (Jurnal Kedokteran Klinik), 2017)
The sources of Â drinking water should be qualified both in chemistry, physics, radioactive or bacteriological. One of the parameters in terms of the quality of water is the amount of deposits of minerals such as calcium and magnesium ions. Water consumption of high calcium can increase urine calcium excretion and the process of early occurrence of kidney stones. This research aims to analyze the difference of urinary calcium excretion in children based on the consumption of well water, bottled water and water from a drinking water company and there is not kristaluria. The design of the study was observational, analytic approach to cut the latitude. This research was conducted in three places, on the island of Gangga, Manado and Bitung in April until the month of November 2016. Urinary calcium excretion was measured by calculating the ratio of urine calcium against creatinin urine. And measured also levels of calcium in drinking water. Data were analyzed with Anova test followed by the Fisher test is meaningful and logistical regression. The result p 0.05 was considered meaningful <. On this research obtained 112 children met the criteria of inclusion, the mean excretion of urinary calcium is obtained from the overall sample is 0.143 mg/dl. There is a very meaningful distinction between samples mengkonsumi water Company drinking water and bottled water as well as samples that consume water Company drinking water and well water with a value of p < 0.0001. In the sample who consume bottled water and well water not obtained urine calcium excretion that difference means p = 0.073. In this study also brings about the relationship between calcium excretion meaning apparent urine hiperkalsiuria of events. These relationships meet the logistical regression equations p = 1/1 + e (0,722-+4, 55x). From this research it can be concluded that calcium levels from each different drinking water and may cause a difference in calcium excretion of urine as well as related events kristaluria. Key words: water, kristaluria, kidney stones